The Great Rebalancing Act : Can Investment Be a Lever in Asia? - Nabar, Malhar (IMF Working Papers; Working Paper ;, 2011)
Ensuring stable growth in the postcrisis world economy will require a rebalancing of economic activity in several countries. In Asia's export-dependent economies, this entails relying more on private domestic demand as a driver of growth. While some countries need to raise consumption, several need to raise investment or reorient it from tradable to nontradable sectors. These changes in investment could be facilitated by financial reforms that enhance domestically oriented firms' access to credit, stronger incentives for corporate restructuring, policies to bolster the business climate and reduce uncertainty, and by improvements in infrastructure that raise the returns to private investment.